Eksistensi Tafsir dari Sudut Objek dan Tujuannya dalam Pengembangan Studi Al-Qur'an - Idrus, Husni; Abu Bakar, Achmad; Basri, Halimah (Al-Aqwam: Jurnal Studi Al-Quran dan Tafsir, 2023)
This study aims to analyze the existence of interpretation from the point of view of its methodology and objectives. This research uses a type of qualitative research with a literature approach that relies on the use of data sources in the form of reputable books and articles to carry out critical analysis by means of content analysis which is the focus of discussion. The steps for analyzing documents in the form of literature start from reconstructing concepts, describing objects, and looking for goals related to interpretation. The results of the study show that the existence of interpretation from the point of view of the object and purpose of tafsir research has made it easier for mufassir and tafsir researchers to understand and interpret the verses of the Qur'an, to ensure that there will be no misunderstandings in interpreting and interpreting these verses; so that in the future the people will be guided properly and correctly in practicing the teachings of Islam, especially in understanding and implementing the verses which he made as divine instructions in the reality of life for both worldly and ukhrawi purposes